Seminoma in Undecended Testis Presenting as an Abdominal Mass: A Case Report (Bangladesh Journal of Urology, 2020)
We report a case in which a 28-year-old infertile bilateral cryptorchoid man with decreased performance status presented to the department of urology with a mildly tender mass in right inguinal region. Both ultrasonography and Computerized axial tomography scan (CT Scan) suggested that the mass arose from right sided undescended testis and left sided testis was normal-sized intrabdominal. His serum á-fetoprotein and LDH were within normal range and only â-hCG was raised 3-fold. He was found azoospermic, his serum LH and FSH were increased but serum testosterone was reduced. The mass was removed by inguinal exploration and histopathology confirmed seminoma of testis. Orchidopexy was done on contralateral side one month after the first operation. A mass in the lower abdomen in a sexually active man with cryptorchoid testis strongly points towards the diagnosis of malignancy in the abdominal testis1. The clinician should aware of it and the urologist should do prompt removal of the tumor and orchidopexy in contralateral side in bilateral case irrespective of age.Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.101-105